English Grammar : (Video Aided Instruction, 2004)
Video Aided Instruction's English Grammar Series makes the tricky rules of English grammar easier to learn than ever before - whether you're new to English or you've been speaking it for years! Perfect for classroom use or self-study, this program uses easy-to-follow examples and practice exercises from everyday life to help you master even the most complicated English grammar topics! It's also great for reviewing forgotten grammar or preparing for many verbal standardized exams such as the SAT, TOEFL, GED, and GRE. Plus, it can really help you improve your grades in school or advance your career! Instead of restating our nouns over and over again, we can use pronouns like "it" and "they" to make our sentences more concise and easier to understand. But mastering this "verbal shorthand" can be tough, since there are many different types and cases of pronouns. This program will help you use pronouns properly! So don't let mistakes in English grammar embarrass you - now you can eliminate them from your speaking and writing forever.